Trends in Mycoplasma pneumoniae infections in pediatric patient preceding, during, and following the COVID-19 pandemic: a comprehensive longitudinal analysis - Jianwei Zhang; Ruoya Wu; Liyan Mo; Jinlong Ding; Ke Huang (Microbiology Spectrum)
ABSTRACT This study investigated the impact of the coronavirus disease 2019 (COVID-19) pandemic and its associated restrictive measures on Mycoplasma pneumoniae infections in children with acute respiratory tract infection. The study aimed to elucidate the epidemiological characteristics of M. pneumoniae infections before and during the pandemic and following the easing of restrictive measures. Pharyngeal secretions were collected from 1,0174 pediatric patients with acute respiratory infection (ARI) who were admitted to Shaoxing Maternity and Child Health Care Hospital (Shaoxing, China) between May 2018 and December 2023. The analysis concentrated on M. pneumoniae detection rates, epidemiological features, and clinical characteristics. Among 10,174 samples collected from 2018 to 2023, 1,060 strains of M. pneumoniae were detected, resulting in an overall positive rate of 10.42% (n = 1,060 out of 1,0176). Further breakdown revealed positive rates of 8.25% (n = 279 out of 3,381) in phase I (May 2018–December 2019), 2.40% (n = 87 out of 3,623) in phase II (January 2020–November 2022), and 21.89% (n = 694 out of 3,170) in phase III (December 2022–December 2023). In comparison to phase I, a noteworthy decline in the positive rate of M. pneumoniae was found during phase II, followed by a substantial increase during phase III (P < 0.05). Furthermore, the positive rate of M. pneumoniae exhibited a significantly greater surge during the summer-autumn period in contrast to the winter-spring (P < 0.05). Additionally, the risk of M. pneumoniae infection in children who aged 7 years surpassed that of the age group of 0–3 years. Throughout the phases preceding, during, and after the COVID-19 pandemic, discernible fluctuations in both age distribution and seasonality of M. pneumoniae infections were identified among hospitalized children with ARI in the East China.IMPORTANCEThe resemblance between the transmission pathways of M. pneumoniae and those of COVID-19 suggests that non-pharmaceutical interventions may have comparable effects on both. This study aimed to analyze the epidemiological characteristics of children with M. pneumoniae infections in Shaoxing, China, from 2018 to 2023. This study explored how the COVID-19 pandemic has influenced the prevalence of M. pneumoniae and provided guidance for disease treatment and infection prevention.